Biomechanical and clinical comparison of different prosthetic in reconstruction following total en bloc spondylectomy in the thoracolumbar spine: based on finite element analysis and clinical data - Gu, Zhangui; Ma, Long; Liu, Qiang; Wang, Kun; Yang, Zongqiang; Niu, Ningkui; Shi, Jiandang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesTo analyze and compare the biomechanical differences and clinical efficacy of artificial vertebral bodies (AVBs) versus traditional titanium mesh cages (TMCs) reconstruction following total en bloc spondylectomy (TES).Materials and MethodsFinite Element Analysis: A finite element model of T12-L5 vertebrae from a healthy adult was utilized to construct two reconstruction models following L2 TES: Group A (AVB) and Group B (TMC). Using ANSYS software, flexion-extension, lateral bending, and axial rotation loading conditions were simulated to comparatively analyze stress distribution at the prosthesis-endplate interface and biomechanical characteristics of the fixation system; Clinical research: This retrospective study included 20 thoracolumbar tumor patients who underwent posterior TES at our institution from January 2014 to October 2024, divided into AVBs (n = 10) and TMCs (n = 10) reconstruction groups. Systematic comparisons were performed for perioperative parameters (operative time, blood loss, hospital stay), with dynamic assessments of preoperative to final follow-up Visual Analog Scale (VAS) pain scores, American Spinal Injury Association (ASIA) neurological classifications, and Karnofsky Performance Status (KPS) scores. Radiographic measurements of vertebral height and angular alignment changes were conducted to comprehensively evaluate reconstruction outcomes.ResultsFinite element analysis revealed that the TMC model exhibited significant stress concentration phenomena across all motion modes compared to the AVB model. Specifically, the stress on the L1 inferior endplate was 50.09%, 17.48%, 74.07%, 133.83%, and 87.23% higher during extension, left lateral bending, right lateral bending, left axial rotation, and right axial rotation, respectively. The L3 superior endplate demonstrated similar stress patterns but with smaller magnitudes. In both implant models, peak stresses occurred during extension and axial rotation, followed by lateral bending, with minimal stress observed during flexion. For the posterior fixation system, no significant differences in maximum stress were observed between the two prosthetic configurations; Clinically, Group A demonstrated significantly lower implant subsidence rates (10% vs 70%) and superior outcomes in intervertebral height loss (1.33 ± 0.82 mm vs 12.36 ± 7.79 mm) and angular loss (p < 0.05). No statistically significant differences were identified between groups regarding hospitalization duration, operative time, intraoperative blood loss, VAS scores, KPS scores, or ASIA grade improvements (p > 0.05).ConclusionFollowing TES, the AVB demonstrated more uniform stress distribution and superior biomechanical performance compared to the TMC. Additionally, the AVB effectively reduced implant subsidence rates, maintained intervertebral height, corrected kyphotic deformities, and exhibited enhanced biomechanical stability and clinical efficacy.